A Meta-Analysis of Use of Serious Games in Education over a Decade - Yu Zhonggen (International Journal of Computer Games Technology)
It seems necessary to review the literature to explore the effectiveness of serious games in education, since the number of studies on serious games is surging up. This study systematically reviewed the literature within around a recent decade. The trend of the number of publications related to use of serious games in education was firstly clarified based on the data retrieved from major databases. Secondly, various factors were determined that influenced the effect of serious game assisted learning. The major section identified both advantages and disadvantages of use of serious games in education. Use of serious games in medical science has been rising in a recent decade, which is thus highlighted in this study. Attitudes toward use of serious games in education were explored, as well as the new development of use of serious games in education. Future theoretical and practical exploration might need interdisciplinary cooperation.